Symmetrically broken rotor bars effect on the stator current of squirrel-cage induction motor - (:unkn) unknown (WYDAWNICTWO SIGMA-N O T SP Z O O, 2011)
End rings and broken rotor bars are common faults in squirrel cage induction motors. For this purpose various broken rotor bars would have been obtained on a special designed rotor of a squirrel cage induction motor. Desired real current data of the broken bars through rings and brushes special designed a squirrel cage of induction motor have been measure. In this study, a three-phase with special designed rotor of a faulty squirrel cage induction motor have been run under nominal load. Stator current wave form analysis has been obtained. This obtained data are compared with stator current of the healthy condition of the rotor bars. The effects of the faults over the stator currents are investigated.
Keywords: Induction motor; rotor bar break; rotor harmonics; symmetric broken effect